Guidance and Counseling in the Independent Learning Curriculum - Amalina, Nabilla Nur; Isnia, Nina; Fikri, Muhammad; Rifky, Muhammad; Ardimen, Ardimen; Tanjung, Romi Fajar (International Journal of Research in Counseling, 2023)
The independent learning curriculum is a follow-up program or innovation from the 2013 curriculum. Guidance and counseling services take a role and make the 2013 curriculum successful because the independent learning curriculum focuses on talents and interests. The purpose of this research is to explore the independent learning curriculum policy and its implications for guidance and counseling services. The research method uses a literature review. Data analysis by reviewing various reference books, journals and other relevant documents. The finding is that the independent learning curriculum is the result of an evaluation of the previous curriculum and the cooperation of all parties is needed to make the independent learning curriculum successful so that it can be established as a tested national curriculum in 2024.